Coviability of Social and Ecological Systems : Reconnecting Mankind to the Biosphere in an Era of Global Change : Vol.1 : The Foundations of a New Paradigm /: Reconnecting Mankind to the Biosphere in an Era of Global Change : Vol.1 : The Foundations of a New Paradigm. (2019) - Unknown
No abstract available